Increasing community engagement in collective impact approaches to advance social change. Issue 1 (1st January 2020) - O'Neill, Moira
ABSTRACT: The Oakland Unified School District (OUSD) is a large urban school district in Oakland, California where hunger and poor nutrition are prevalent. Given the critical link between nutrition and academic achievement, OUSD pursued a collective impact approach to school food reform called Rethinking School Lunch Oakland (RSLO) as part of OUSD's community development model of school reform, with the Center for Ecoliteracy and philanthropy. RSLO required repurposing land among other major system shifts. This case study describes RSLO's implementation, the engagement through expanded public processes, and how OUSD's legal identity prevented shared decision-making over land use – one of the most important issues for community given past land use and current neighborhood change. This case study illustrates how past application of law and a government collaborator's legal identity, structure, and relationship to other government entities and community will shape engagement and the Collective Impact (CI) approach.